Size and Morphology Investigation of PZT Nanofibers for Energy Harvesting Applications using Digital Holography - Suwan Plaipichit; Surawut Wicharn; Chokchai Puttharugsa; Patamas Bintachitt; Areeya Aeimbhu; Prathan Buranasiri (My University, 2025)
Polyvinylidene fluoride fibers composed of piezoelectric lead zirconate titanate under different fabrication conditions were investigated using digital holography technique. Larger PZT content and larger feed rates results in larger diameters, and thicker fibers respectively.
Keywords: Innovative Energy Harvesting Technologies; Digital Holography and Microscopy; Photorefractive and Nonlinear Optics